Long-term outcomes of a phase II trial of moderate hypofractionated image-guided intensity modulated radiotherapy (IG-IMRT) for localized prostate cancer. Issue 1 (January 2017) - Lieng, Hester; Pintilie, Melania; Bayley, Andrew; Berlin, Alejandro; Bristow, Robert; Chung, Peter; Gospodarowicz, Mary; Huang, Roger; Ménard, Cynthia; Warde, Padraig; Catton, Charles
Abstract: Purpose: To evaluate long-term radiation toxicity and biochemical control of two moderately hypofractionated radiotherapy regimens for prostate cancer. Material and methods: Eligible men with localized prostate cancer received image-guided intensity modulated radiotherapy (IG-IMRT) to a dose of 60 or 66 Gy in 3 Gy fractions in a phase II trial. Endpoints included late gastrointestinal (GI) and genitourinary (GU) toxicity and biochemical failure (FFBF). Results: Ninety-six men received 60 Gy and 27 received 66 Gy. Accrual to the 66 Gy cohort terminated early due to excessive Grade 3–4 late toxicity. Median follow-up was 128 months (60 Gy) and 108 months (66 Gy). In the 60 Gy cohort, cumulative late Grade ⩾2 GI and GU toxicity at 8 years was 4% and 12% respectively. In the 66 Gy cohort, late Grade ⩾2 GI and GU toxicity was 21% and 4% respectively at 8 years. The 5- and 8-year FFBF for 60 Gy was 81% and 66%, and for 66 Gy was 88% and 80%. Conclusions: Moderate hypofractionation with IG-IMRT to 60 Gy was associated with favorable late toxicity although late urinary toxicity and biochemical failures were observed beyond 5 years. Dose escalation to 66 Gy was associated with significantly worse late toxicity.